Implications of the use of 1-hour post-load plasma glucose value during an oral glucose tolerance test (OGTT) for the diagnosis of dysglycemia among a cohort of high-risk Thai people - Thewjitcharoen, Yotsapon; Chatchomchuan, Waralee; Wanothayaroj, Ekgaluck; Butadej, Siriwan; Prasartkaew, Hussamon; Nakasatien, Soontaree; Krittiyawong, Sirinate; Himathongkam, Thep (Diabetes research and clinical practice, 2025)
Implications of the use of 1-hour post-load plasma glucose value during an oral glucose tolerance test (OGTT) for the diagnosis of dysglycemia among a cohort of high-risk Thai people. The recent International Diabetes Federation (IDF) statement recommended using the 1-hour plasma glucose (1-h PG) during oral glucose tolerance test (OGTT) for diagnosing dysglycemia. This study aimed to examine the prevalence of dysglycemia among high-risk Thai people. An 18-year retrospective study of Thai people who underwent OGTT procedures in routine clinical setting was analyzed. A total of 1,203 subjects (age 50.3 ± 13.0 years, BMI of 26.3 ± 4.9 kg/m2, HbA1c 5.7 ± 0.5 %) were reviewed. Based on traditional OGTT criteria, impaired glucose tolerance (IGT) was found in 36.6 %, and diabetes (DM) in 16.8 % of the subjects. An elevated 1-h PG was found in 40.6 % of normal glucose tolerance (NGT) people, and 3.4 % of them would be classified as DM based on the IDF OGTT criteria. Among IGT people, 40.9 % would be classified as DM per the IDF criteria. The prevalence of DM was more than two times higher with the IDF OGTT criteria When the proposed 1-hr OGTT criteria was used as a reference standard, the optimal HbA1c cut-off point to diagnose diabetes was at 5.9 % which was much lower than the current HbA1c-based criteria of diabetes. Diabetes prevalence is more than 2 times higher when diagnosed with the IDF OGTT criteria in high-risk Thai people. Overt DM by the IDF OGTT would be missed for almost 5 times by using the HbA1c level alone.